2011
DOI: 10.1007/s11097-010-9190-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroaesthetics and beyond: new horizons in applying the science of the brain to the art of dance

Abstract: Throughout history, dance has maintained a critical presence across all human cultures, defying barriers of class, race, and status. How dance has synergistically co-evolved with humans has fueled a rich debate on the function of art and the essence of aesthetic experience, engaging numerous artists, historians, philosophers, and scientists. While dance shares many features with other art forms, one attribute unique to dance is that it is most commonly expressed with the human body. Because of this, social sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 50 publications
2
58
1
2
Order By: Relevance
“…Previous studies have shown that watching the moving body of other individuals implies mapping their motor, sensory and emotional states onto the observer's bodily states and that this shared representation is one of the source of body aesthetic appreciation (for review, see Cross & Ticini, 2012;Ticini et al, 2015;Freedberg & Gallese 2007). The extension of this shared representation is dependent upon the commonalities of action (i.e., motor repertoire; Calvo-Merino et al, 2005;Aglioti et al, 2008;Makris & Urgesi, 2015) and form (i.e., ethnicity; Müller et al 2011;Avenanti et al, 2010) parameters between the observed and the observer's body.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that watching the moving body of other individuals implies mapping their motor, sensory and emotional states onto the observer's bodily states and that this shared representation is one of the source of body aesthetic appreciation (for review, see Cross & Ticini, 2012;Ticini et al, 2015;Freedberg & Gallese 2007). The extension of this shared representation is dependent upon the commonalities of action (i.e., motor repertoire; Calvo-Merino et al, 2005;Aglioti et al, 2008;Makris & Urgesi, 2015) and form (i.e., ethnicity; Müller et al 2011;Avenanti et al, 2010) parameters between the observed and the observer's body.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other dimensions were relevant in specific domains, for example interestingness and suspensefulness in literature (Knoop et al, 2016). While similar semantic analyses are lacking in the domain of body aesthetics, the "liking" dimension has been widely used in neuroscientific study of the appreciation of the human body, for example in dance, (Kirsch et al, 2015;Cross and Ticini, 2012) and it has been associated to the processing of essential kinematics aspects of the movements, such as speed, and movement direction, at both behavioural and brain levels (Calvo-Merino et al, 2008;Cross et al, 2011).…”
Section: Limitations and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on movement qualities has shown that training in perceiving movement is pivotal for how movement is engaged in human-computer interaction (Mentis & Johansson, 2013). Similarly, in neuroscience findings point to that human perception and understanding of movement is conditioned by whether the person themselves have performed the movement (Cross & Ticini, 2012). In our projects, it was thus fundamental not to try and impose meaning upon the movements that were being created.…”
Section: Introductionmentioning
confidence: 85%
“…(Cross 2011;7) Si se entiende de este modo, un paradigma neuro-biológico no es una reducción o una simplificación de ninguna manera sino un añadido desde la evidencia a la compleja reflexión sobre la condición del conocimiento, o si se quiere, sobre las condiciones en las que el conocimiento es posible.…”
Section: Daimon Revista Internacional De Filosofía Suplemento 5 (2016)unclassified